Knowledge management: another management fad? - Leonard J. Ponzi; Michael Koenig (Information Research: An International Electronic Journal)
Knowledge management is a subject of a growth body of literature. While capturing the interest of practitioners and scholars in the mid-1990s, knowledge management remains a broadly defined concept with faddish characteristics. Based on annual counts of article retrieved from Science Citation Index, Social Science Citation Index, and ABI Inform referring to three previous recognized management fad, this paper introduces empirical evidence that proposes that a typical management movement generally reveals itself as a fad in approximately five years. In applying this approach and assumption to the case of knowledge management, the findings suggest that knowledge management is at least living longer than typical fads and perhaps is in the process of establishing itself as a new aspect of management. To further the understanding of knowledge management's development, its interdisciplinary activity and breadth are reported and briefly discussed.